The Assessment of Mixing Solid Waste from Palm Kernel Cake and Indigofera Zollingeriana as Chicken Feed towards the Free-Range Chicken Growth Rate - Ali Zainal-Abidin, Mohamad Termizi; Abdul Syukor, Abd Razak; Muhammad Amirul Syafiq, Nasarudin; Nurul Farah Anisa, Hairolnizam; Farah Amalina, Ishak; Suryati, Sulaiman; Mohd Rashid, Ab Hamid; Noraini, Samat (Penerbit UMP, 2024)
This study is to determine the characteristics of the palm kernel cake (PKC) and Indigofera zollingeriana and its suitability as the ingredients for animal feed. This study focuses on the chicken feed formulation optimization with mixture of the solid waste and the Indigofera zollingeriana. This study also investigates the effect of the formulated chicken feed towards the growth of the chicken within the experimental duration. The formulated chicken feed with palm kernel cake and Indigofera zollingeriana have the nutrients needed for the chicken to grow healthily and this shows that the agro-industrial waste can substitute the corn as the main ingredient in chicken feed.